Religious soundscapes and traumatic listening: auditory memory, ritual, and spiritual space in Chong Keat Aun's Snow in Midsummer (2023) - Jiang, Xingyao; Suboh, Rosdeen bin (Frontiers in Communication, 2025)
This study investigates how religious soundscapes mediate historical trauma in Snow in Midsummer (2023), directed by Malaysian Chinese filmmaker Chong Keat Aun. Focusing on Ah Eng's auditory journey to locate the graves of her father and brother lost in the 1969 May 13 Incident, the film interweaves personal grief, collective memory, and spectral presence. The research applies a sound-oriented close textual analysis, in which auditory events are systematically annotated and archived with timecodes, categorized into religious, spectral, and environmental sounds, and then examined through semiotic and contextual analysis. Interdisciplinary theories from trauma studies, sound anthropology, and religious aesthetics, together with Malay-language historical materials, inform the interpretations. The analysis reveals that sonic elements such as the adhan, Buddhist bells, and Taoist rituals transcend multicultural reflection by generating a cross-cultural acoustic space that resists political amnesia. In doing so, the film stages a form of sonic memory work where mourning converges with resistance and ritual with historical critique, offering an ethics of listening rooted in spiritual hybridity and emotional resonance that allows the voices of the dead to reverberate within Malaysia's postcolonial soundscape.